Epidemiologic characteristics of malignant lymphoma in Hubei, China: A single-center 5-year retrospective study. Issue 35 (August 2018) - Meng, Jingshu; Chang, Chan; Pan, Huaxiong; Zhu, Fang; Xiao, Yin; Liu, Tao; Nie, Xiu; Wu, Gang; Zhang, Liling
Abstract : Abstract: Distribution of different malignant lymphoma subtypes varies substantially in different geographic regions, even in different districts in China. In order to estimate the epidemiologic characteristics of malignant lymphoma in Hubei, China, we retrospectively analyzed a total number of 2027 newly diagnosed cases from April 2009 to April 2014 in a single institution according to the 2008 WHO classification. The median diagnosis age of all these lymphoma patients was 53 (1–99) years, and the median ages for non-(NHL) and Hodgkin lymphoma (HL) were 54 (1–99) years and 38 (5–84) years, respectively. Among the included patients, mature B-cell neoplasms occupied 61.3%, mature T- and NK-cell neoplasms accounted for 21.0%, precursor lymphoid cell neoplasms made up 4.5%, and HL constituted 8.0%. The most common subtype of NHL was diffuse large B cell lymphoma (41.3%), followed by NK/T cell lymphoma (13.4%), extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) (8.0%), follicular lymphoma (6.6%), lymphoblastic lymphoma (4.9%), and mantle cell lymphoma (4.0%). Mixed cellularity lymphoma ranked first among classical HL subtypes, and there is a bimodal median age distribution revealed by our study, which is different from results reported by other regions of China. Most subtypes revealed male predominance while MALT lymphoma showed a slight female predominance. Extranodal lymphomas most frequently involved gastrointestinal tract, sinonasal region, and Waldeyer ring. In summary, the distribution of lymphoma subtypes in Hubei of China is similar to that of Asian populations, as well as other regions of China, but distinct from the Western countries.